Distribution of gastrointestinal helminthosis of small ruminants in Ibadan, South Western Nigeria: Role of traditional rearing system (2014)
In Nigeria, where the great majority of herds are managed traditionally, the search for feed and water results in scavenging livestock-raising methods. This often exposes such animals to high levels of infections, causing considerable losses. A survey was conducted during the short wet season to determine the prevalence and role of factors associated with small ruminant helminthosis in Ibadan region. A total of 880 sheep and goats were examined using standard parasitological procedures. The overall prevalence of helminthosis was 92.7%. Species prevalence of helminthosis was 96.1% and 89.3% in sheep and goats respectively. Sex prevalence was 94.1% and 87.8% in females and males respectively. Peri-urban prevalence was 96.0% while urban had 88.8% of mixed helminth infection. It was also observed that 42.5% and 57.7% of animal owners in urban and peri-urban areas lacked knowledge of anthelmintic used. Others, 20% and 30% of urban and periurban owners expressed some knowledge of existence of worms but believed that scavenging animals when infected have innate ability to seek medicinal herbs and plants to graze on. A total of 10% of all owners interviewed are aware that veterinary care should be given but only when the animals are obviously sick or fail to thrive. Our results reveal that the entire Ibadan region is endemic for gastrointestinal helminthosis and owners in the region believe that the best system for rearing small ruminants is the extensive management. [Adediran OA, Adebiyi Al, Uwalaka EC. Distribution of Gastrointestinal Helminthosis of Small Ruminants in Ibadan, South Western Nigeria: Role of Traditional Rearing System.